Gambaran Pelaksanaan Spiritualitas Sholat Pasien Anak "Y" di Ruang Rawat Inap RS PKU Bantul - Aryiani, Ryian; Ani Yuniarti, Falasifah (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2026)
Spirituality is a fundamental human need that is inseparable from holistic healthcare. Illness and hospitalization affect not only the physical aspect but also the spiritual dimension, including the patient's ability to perform religious worship. This study aims to provide an in-depth description of prayer (sholat) spirituality practice among a pediatric patient during inpatient care at PKU Muhammadiyah Bantul Hospital. A qualitative approach with a descriptive case study design was employed. The research subject was a single female pediatric patient, identified as "Y", aged 17 years, Muslim, hospitalized due to febris. Data were collected through semi-structured in-depth interviews, direct observation, and document review in September 2025. Data analysis followed Braun and Clarke's (2022) thematic analysis framework, with trustworthiness ensured through source triangulation and member checking. Analysis yielded four main themes: (1) early internalization of religious values shaped by family and Islamic boarding school environments; (2) prayer as a source of psychological calm and strength during illness; (3) barriers to worship practice, including physical weakness, pain, and difficulties in ritual purification (thaharah); and (4) positive spiritual meaning-making of illness, perceived as a divine trial, a means of sin remission, and a catalyst for spiritual closeness to God. The findings indicate that despite physical limitations, the patient maintained strong spiritual motivation by positively reframing her illness experience. Nurses are encouraged to actively assess and facilitate spiritual needs, including informing patients about religious dispensations (rukhsah), as an integral component of holistic nursing care for Muslim pediatric patients